2017
DOI: 10.1063/1.4977855
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium and dynamic pleating of a crystalline bonded network

Abstract: We describe a phase transition that gives rise to structurally non-trivial states in a two-dimensional ordered network of particles connected by harmonic bonds. Monte Carlo simulations reveal that the network supports, apart from the homogeneous phase, a number of heterogeneous "pleated" phases, which can be stabilised by an external field. This field is conjugate to a global collective variable quantifying "non-affineness", i.e. the deviation of local particle displacements from local affine deformation. In t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 31 publications
2
29
0
Order By: Relevance
“…For solids where individual particles can be distinguished and tracked, one should be able to realise h X in the laboratory and check our predictions in the full h X − ε plane. Indeed, it has already been discussed in detail [15,17,20] how this may be accomplished in the future for colloidal particles in 2d using dynamic laser traps. Briefly, the set of reference coordinates is read in and a laser tweezer is used to exert additional forces, F χ (r i ) = −∂H X /∂r i to each particle i which bias displacement fluctuations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For solids where individual particles can be distinguished and tracked, one should be able to realise h X in the laboratory and check our predictions in the full h X − ε plane. Indeed, it has already been discussed in detail [15,17,20] how this may be accomplished in the future for colloidal particles in 2d using dynamic laser traps. Briefly, the set of reference coordinates is read in and a laser tweezer is used to exert additional forces, F χ (r i ) = −∂H X /∂r i to each particle i which bias displacement fluctuations.…”
Section: Discussionmentioning
confidence: 99%
“…For our results of the equilibrium structures and transitions at T > 0 we employed the sequential umbrella sampling (SUS) technique (see Appendix C) coupled to Monte Carlo [22,23] in the constant number N , area A = L x × L y , ε and temperature T ensemble. Advanced sampling techniques such as SUS are necessary to overcome the large barriers between the N and M phases, enabling the equilibrium transition to be observed [17]. We show results for T = 0.8 and density ρ = 1.1547, corresponding to the choice a = 1.0 for the lattice parameter.…”
Section: The Equilibrium First Order Phase Transitionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our calculations explicitly take into account the effect of finite temperature T > 0 and therefore represent a definite advance on earlier work. We show that ripplocation like structures, which are the generalization of the purely two-dimensional (2D) pleats studied earlier [12,13], readily form following a phase transition from an essentially flat sheet containing at most thermally generated ripples. These phases co-exist at a first-order boundary.…”
Section: Introductionmentioning
confidence: 76%
“…Recently, it has been observed that spatially confined flexible membranes deform by reorganizing their morphology to form hierarchical structures of great complexity [6]. Wrinkles, ripples, folds [7][8][9][10][11], as well as higher order structures like pleats [12,13] are ubiquitous both in nature and in emergent technology. They have been observed in biological tissues [14,15], polymer sheets [16], and many other lowdimensional materials involving flexible sheets and membranes [17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%